Legal Vacuums: The Challenge of Protection for Climate Refugees - Sabirin, Ahmad; Bayuaji, Anandayu Pavita; Keumala, Dinda (Lampung Journal of International Law, 2024)
Climate change has triggered massive migrations known as climate refugees, individuals who have been forced to leave their homes due to natural disasters and deteriorating environmental conditions. However, the legal vacuum protecting climate refugees is an urgent issue. This article discusses the need to establish new conventions or protocols that specifically regulate the status and safety of refugees due to climate change. The research method is a normative juridical approach analysing applicable legal regulations and relevant case studies. The new convention should clearly define climate refugees, establish their fundamental rights, and affirm the principle of non-refoulement to protect them from deportation to dangerous areas. In addition, the state's responsibility in providing protection and funding mechanisms must also be regulated. While challenges such as disagreements between countries and a lack of awareness remain, global initiatives show progress toward better protection for climate refugees. As such, it is hoped that the new legal framework can provide legal clarity and ensure that the rights of climate refugees are recognised and protected internationally.